How can the process of professional identity formation of a gender-affirming practitioner inform medical curriculum change? - De Vries, Elsje (Department of Health Sciences Education, 2025)
Background Transgender and gender diverse people experience significant health disparities. Health professionals are generally not adequately prepared by current curricula to provide gender-affirming, holistic care that is respectful of patients' gender identity. Therefore, this study asks the question: How can the professional identity formation of a gender-affirming practitioner inform medical curriculum change? Methodology The objectives of the study were to: a. Analyse the process of professional identity formation of gender-affirming health care practitioners and students, using narrative interviews. b. Illuminate how medical curriculum change can enable gender-affirming professional identity formation. A critical research paradigm using the conceptual lens of professional identity formation was adopted. Case study design and narrative inquiry were the complementary methodological frameworks used. The study was conducted in two phases. In Phase One, six health care practitioners and nine medical students described their shared their experiences of becoming gender-affirming practitioners through narrative interviews. A narrative analysis was conducted and represented as stories. In phase two these stories were shared with medical educators in a group engagement to facilitate their reflections on gender-affirming curriculum change. Reflexive thematic analysis was used to analyse this discussion. Regulatory policy and university curriculum documents were analysed. Other data sources were participant reflective journals from phase one and the researcher's reflective journal. Findings from each phase were combined for the case study analysis using a critical lens. Findings The process of professional identity formation is described as a journey of becoming over time rather than a destination. Being gender-affirming entails providing holistic care, confronting pathologising perspectives, seeing the human first, and shifting power to enable patient participation. The present learning environment at medical schools is not conducive to the development of a gender-affirming practitioner, given the gap between the intended and experienced curriculum. Conclusion A gender-affirming approach offers a new perspective of how power dynamics may shift to create a more enabling environment for the development of a genderaffirming professional identity. Curriculum change can facilitate this approach by integrating gender-affirming healthcare into the medical curriculum with a focus on attitudes, cultural humility and incorporating the voices of transgender and gender diverse people